Social Support and Coping Style of Medical Residents in China: The Mediating Role of Psychological Resilience - Xu, Chao; Wang, Yongyi; Wang, Zongqin; Li, Biao; Yan, Chuandong; Zhang, Sheng; Chen, Bei; Zhang, Di; Peng, Juan (Frontiers in Psychiatry, 2022)
Objectives: Recent surveys have paid insufficient attention to the psychological status of residents, but residents, as a special group of medical workers, need to be focused on. This study aimed to investigate residents' levels of social support, psychological resilience, and coping style, and explore the mediating role of psychological resilience, which can ultimately provide a new theoretical basis for improving residents' psychological status and quality of work and life. Methods: A total of 577 residents from China were investigated by an online questionnaire, using convenience sampling. Associations between social support, psychological resilience, and coping styles were assessed using Pearson correlation analysis. The mediating effect of psychological resilience was tested using SPSS Process. Results: Positive correlations between social support, psychological resilience and coping style were found (r = 0.474, P < 0.001; r = 0.473, P < 0.001; r = 0.353, P < 0.001). The mediating effect of psychological resilience in the relationship between social support and coping style was significant (95% CI: 0.168, 0.384), and accounted for 25.84%. Conclusion: Attention should be paid to the psychological status of residents, and social support and psychological flexibility can be used to increase the enthusiasm for their coping style and promote their mental health.